The Bible, Religion, and Power in Margaret Atwood’s The Handmaid’s Tale A Close Reading from the Perspective of Biblical Scholarship - Hartenstein, Friedhelm (Journal for Religion, Film and Media)
This article offers a close reading of Atwood’s famous novel from the perspective of biblical scholarship. Anyone who reads The Handmaid’s Tale will readily notice how strongly biblical texts inform the narrative and the fictional world of Gilead. This relationship begins with Genesis 30:1–3, which appears as an epigraph. Religion in all its complexity is a cornerstone of the novel. The article looks at its threefold use of religion: as a biblically based foundation of the ideology and power structures of Gilead, as an anthropological foil for the leitmotif of seeing and being seen in Offred’s story, and as a point of departure and reference for the main character’s personal reflections. The article limits itself to observations based on the novel as first published in 1985.